Neutrino scattering off the 95,97Mo isotopes - Balasi, K. G.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2020)
In this work we perform calculations of the cross sections for neutral-current neutrino scattering off the 95,97Mo isotopes. Both the incoherent and coherent con- tributions to the cross sections are considered. The wave functions of the initial and final nuclear states are constructed in the context of the quasiparticle phonon model (MQPM). The response of the aformentioned nuclei to supernova neutrinos are computed by folding the obtained cross sections with a two-parameter Fermi-Dirac distribution.